Health Perspective of Local and United Nation Personnel Reported in Bangladesh Level-II Hospital in Liberia (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Liberia is one of civil war-ravaged country, where peace process started by United Nation (UN) in 2003. Bangladesh is also included in peacekeeper’s mission including medical services and sent a Level-II Hospital named Banmed 10 which started works in Liberia in June 2013 and provide medical support to UN personnel as well as local people and civil military cooperation (CIMIC). Pictures of health problems of these personnel are drawn in this study.Objectives: To find out the disease pattern of natives and multinational UN personnel as well as local people visiting Level- II Hospital, Banmed-10.Materials and Methods: It was a descriptive type of observational study conducted among 6906 patients from 18 Jun 2013 to 31 March 2014. Data were collected from the outdoor/indoor medical records and documents. Relevant data are sorted out and entered in computer for necessary calculation. Results are arranged in appropriate tables showing percent or proportion.Results: Common diseases are found in UN personnel and Liberians such as Fever (Nos), Malaria, RTI, Diarrhoea, Backache, Arthritics, Hernia and others. Fever (Nos) most common 83.7% among the locals and 65.3% among the UN personnel. Malaria 16.3% among the locals and 11.3% among the UN personnel. Some special cases were also found like Lassa and Ebola.Conclusion: Bangladesh level-II Hospital has been providing medical support to UNMIL personnel as well as to local people as they are highly dependent on it due to heavy destruction of their medical facilities during civil war. Bangladesh earns commendable reputation by their high professionalism, quality service and dedication to the responsibility.JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 52-56